2018
DOI: 10.1159/000491442
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, Evaluation, Management, and Outcomes of Acute Stroke in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis

Abstract: Aims: We performed a systematic review to evaluate stroke presentation, evaluation, management, and outcomes among studies conducted in low- and middle-income countries (LMIC). Methods: We searched MEDLINE (Ovid), Embase (Elsevier), and the Global Health (EBSCOhost) databases between January 2005 and June 2017 for studies conducted in LMICs defined by the World Bank. We pooled prevalence estimates using an inverse-variance weighting method and stratified by the country income group. Results: The search identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…[2,9] In low-income countries, the reported prevalence of risk factors among patients with stroke is lower, however patients have the highest in-hospital mortality, probably due to delays in presentation for seeking acute stroke care, differences in health system response and acute stroke management. [10]…”
mentioning
confidence: 99%
“…[2,9] In low-income countries, the reported prevalence of risk factors among patients with stroke is lower, however patients have the highest in-hospital mortality, probably due to delays in presentation for seeking acute stroke care, differences in health system response and acute stroke management. [10]…”
mentioning
confidence: 99%
“…Thisintegrative review data showed stroke is an important public-health problemand should be a significantpart of the public-health agenda, mainly in low and middle-countries 36 .The studyhas compiled data on high-quality evidence-based clinical practice guidelines that can provide a way to bridge the gap between public policy and best practices in local contexts. The importance of monitoring deaths, risk factors, hospitalizations and, efforts needed to improve health services destined to take care of patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Tins et al (2013) reported the Brazilian challenges and experiences in the implementation of the National Stroke Project 7 . Cooperation between states and municipalities leads to development of local acute stroke prevention plans, by promoting public health and social inclusion actions, consistent with the principles af the Brazilian Unified Health System 4,5,19,21,23,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, reperfusion treatments (thrombolysis) were administered only to 1–8% of the admitted patients [70]. A recent meta-analysis showed that only 3% (95% CI 2–4%) of patients were thrombolysed [71].…”
Section: Discussionmentioning
confidence: 99%